# 0.5(4z+5)+6.5=0.6(4z-5)

## Simple and best practice solution for 0.5(4z+5)+6.5=0.6(4z-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 0.5(4z+5)+6.5=0.6(4z-5) equation:

Simplifying
0.5(4z + 5) + 6.5 = 0.6(4z + -5)
Reorder the terms:
0.5(5 + 4z) + 6.5 = 0.6(4z + -5)
(5 * 0.5 + 4z * 0.5) + 6.5 = 0.6(4z + -5)
(2.5 + 2z) + 6.5 = 0.6(4z + -5)
Reorder the terms:
2.5 + 6.5 + 2z = 0.6(4z + -5)
Combine like terms: 2.5 + 6.5 = 9
9 + 2z = 0.6(4z + -5)
Reorder the terms:
9 + 2z = 0.6(-5 + 4z)
9 + 2z = (-5 * 0.6 + 4z * 0.6)
9 + 2z = (-3 + 2.4z)
Solving
9 + 2z = -3 + 2.4z
Solving for variable 'z'.
Move all terms containing z to the left, all other terms to the right.
Add '-2.4z' to each side of the equation.
9 + 2z + -2.4z = -3 + 2.4z + -2.4z
Combine like terms: 2z + -2.4z = -0.4z
9 + -0.4z = -3 + 2.4z + -2.4z
Combine like terms: 2.4z + -2.4z = 0.0
9 + -0.4z = -3 + 0.0
9 + -0.4z = -3
Add '-9' to each side of the equation.
9 + -9 + -0.4z = -3 + -9
Combine like terms: 9 + -9 = 0
0 + -0.4z = -3 + -9
-0.4z = -3 + -9
Combine like terms: -3 + -9 = -12
-0.4z = -12
Divide each side by '-0.4'.
z = 30
Simplifying
z = 30`